La Grammaire au Service de la Galanterie? Analyse de Les « Vous » et les « Tu » de Voltaire - Dubois, Françoise Paulet (Linguistica Atlantica, 2009)
In his epistle Les "Vous" et les "Tu", Voltaire calls his sweetheart "tu" and "valls" alternately. He could use the familiar address when she was young and unambitious, but now that she has become a rich and distant lady, this familiarity is not possible anymore. This alternation of formal and infonnal address, analysed in the light of the theory of politeness, evokes the many, someti.rncs contradictory, values of these two pronouns .